Evaluation of the results of sub axial cervical spine injury with incomplete neurology treated by posterior lateral mass fixation with screws and rod and fusion by bone graft - Zia-Ur-Rahman, M.; Bhakta, Ananta Kumar; Mondol, Pankoj Kanti; Khan, M. Tanvir Ahasan Juglol; Sadi, Sheikh M. Sheikh; Khan, M. Sahidur Rahman; Biswas, Bappy Kumer; Mahbub, S. K. Golam (International Journal of Research in Orthopaedics, 2024)
Background: The cervical spine is a highly mobile segment of the spinal column, liable to a variety of diseases and susceptible to trauma. Lateral mass screw fixation has become the method of choice in stabilizing subaxial cervical spine among other posterior cervical fixation techniques. This study aimed to assess the radiological efficacy of the cervical lateral mass screw insertion and rod fixation by Yoon’s method. Methods: This was a prospective observational study conducted in the Department of Orthopedics, National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR), Dhaka, over a period of two years from July 2014 to June 2016. We included 100 patients who will be admitted with a diagnosis of unstable cervical spine injury during period of study. Results: The mean age of the patients was (36.87±7.45) years. Majority of the patients were male (80%). Bearing load on the head was the most common (40%) cause. Most commonly involved level of injury was C5/C6 (30%) and type of injury was Fracture Subluxation (35%). Hemorrhage (15%) was the most common per operative complication followed by neck pain (12%), superficial infection (10%), screw pull out (10%), and post-operative khyphotic deformity (10%). Evaluation of final outcome revealed 67% and 33% patients had satisfactory & unsatisfactory results respectively. Conclusions: The lateral mass screw insertion and rod fixation is a safe and reliable technique with low rate of complication related to instruments. This method enhances neurological recovery, reduce pain and improve working status with early rehabilitation.